Hubungan Motivasi Belajar Dengan Prestasi Belajar Bahasa Arab Kelas VIII Di MTS Negeri 37 Jakarta. - Sari, Diah Puspita (INTIFA: Journal of Education and Language, 2024)
ABSTRACT This study aims to determine the relationship between learning motivation and Arabic learning achievement among eighth-grade students at MTs Negeri 37 Jakarta. The research uses a quantitative approach with the product moment correlation method assisted by IBM SPSS 23. The population consists of all eighth-grade students with a sample of 31 students. The instrument for collecting learning motivation data was a questionnaire, while Arabic learning achievement data were obtained through documentation of students’ Arabic report card scores. The frequency distribution results show that the tendency of the learning motivation variable falls into the medium category, with 17 students (54.8%) out of 31. Meanwhile, the learning achievement variable tends to be in the low category, with 13 students (41.9%) out of 31. The data analysis results show 0.159 > 0.05, meaning there is no significant relationship between learning motivation and Arabic learning achievement. Even so, there is a positive but weak relationship based on the interpretation table, with learning motivation contributing 6.7% to learning achievement. These results are important as evaluation material for teachers and schools to consider other factors besides motivation that may affect Arabic learning achievement. ABSTRAK Penelitian ini bertujuan untuk mengetahui hubungan antara motivasi belajar dengan prestasi belajar bahasa Arab pada siswa kelas VIII MTs Negeri 37 Jakarta. Pendekatan pada penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasi product moment dan bantuan IBM SPSS 23. Populasi adalah seluruh siswa kelas VIII dengan 31 sampel siswa. Instrumen pengumpulan data motivasi belajar dikumpulkan melalui angket dan prestasi belajar melalui dokumentasi nilai rapor bahasa Arab siswa. Hasil distribusi frekuensi menunjukkan nilai kecenderungan variabel motivasi belajar berada pada kategori sedang yaitu sebanyak 17 siswa (54,8%) dari jumlah sampel sebanyak 31 siswa. Sedangkan variabel prestasi belajar siswa cenderung pada kategori rendah yaitu sebanyak 13 siswa (41,9%) dari jumlah sampel 31 siswa. Hasil analisis data menunjukkan 0,159 > 0,05, artinya tidak terdapat hubungan signifikan antara motivasi belajar dengan prestasi belajar bahasa Arab. Meski begitu, ada hubungan positif berkekuatan rendah berdasarkan tabel interpretasi, dengan motivasi belajar berkontribusi 6,7% terhadap prestasi belajar. Hasil ini penting sebagai bahan evaluasi bagi guru dan sekolah untuk memperhatikan faktor lain selain motivasi yang mungkin jauh lebih berpengaruh terhadap prestasi belajar bahasa Arab.